MANAJEMEN CAPACITY BUILDING TENAGA ADMINISTRASI SEKOLAH DI SEKOLAH LABORATORIUM UPI - Suryana, Asep; Karim, Aim Abdul; Sapriya, Sapriya (PEDAGOGIA, 2017)
School administration personnel as "supplements and complement" in the quality of education services,administrative activities and other support activities have a significant effect on the learning service activities.The purpose of this research is to gain information about the position, and the program development of SchoolAdministration Staff (education and training) at every level in UPI Laboratory School and those who areresponsible for the development of School Administration Staff. The research method used is qualitative with theresearch subject of all administrative staff of school at UPI laboratory school. The result in establishing the TASprofession in UPI related to the clarity of the status of manpower and comprehensively correlated with the statusof school administrative staff at every level of education in the laboratory school. The description of the careerladder of the school administrative staff in the laboratory school is not yet apparent. Built a school administrationprofession is not only an obligation of the administrative staff itself but rather the full support of the school andgovernment.